2020
DOI: 10.1093/toxsci/kfaa081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 5-day In Vivo Rat Liver and Kidney With High-throughput Transcriptomics for Estimating Benchmark Doses of Apical Outcomes

Abstract: A 5-day in vivo rat model was evaluated as an approach to estimate chemical exposures that may pose minimal risk by comparing benchmark dose (BMD) values for transcriptional changes in the liver and kidney to BMD values for toxicological endpoints from traditional toxicity studies. Eighteen chemicals, most having been tested by the NTP in 2-year bioassays, were evaluated. Some of these chemicals are potent hepatotoxicants (e.g. DE71, PFOA, and furan) in rodents, some exhibit toxicity but have minimal hepatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 7 publications
6
53
0
Order By: Relevance
“…The concordance of dam molecular and apical POD values reported here align with published data showing adult rat general toxicity molecular POD values are typically within an order of magnitude of general toxicity apical POD values (Chepelev et al, 2018;Gwinn et al, 2020;Jackson et al, 2014;Johnson et al, 2020;LaRocca et al, 2020;Moffat et al, 2015;Thomas et al, 2011;Thomas et al, 2013). Interestingly, the dam liver molecular POD values were approximately 30X lower than the dam liver apical POD values (Figure 2).…”
Section: Dam Liver and Placenta Mrna And Mirna Point Of Departuresupporting
confidence: 89%
See 3 more Smart Citations
“…The concordance of dam molecular and apical POD values reported here align with published data showing adult rat general toxicity molecular POD values are typically within an order of magnitude of general toxicity apical POD values (Chepelev et al, 2018;Gwinn et al, 2020;Jackson et al, 2014;Johnson et al, 2020;LaRocca et al, 2020;Moffat et al, 2015;Thomas et al, 2011;Thomas et al, 2013). Interestingly, the dam liver molecular POD values were approximately 30X lower than the dam liver apical POD values (Figure 2).…”
Section: Dam Liver and Placenta Mrna And Mirna Point Of Departuresupporting
confidence: 89%
“…Since the pioneering work developing quantitative measures of transcriptome change in toxicology studies (Thomas et al, 2007; Yu et al, 2006), mRNA‐based transcriptome POD values have been compared to traditional apical endpoint POD values across a number of general toxicity studies. These comparisons have led to a developing consensus that a transcriptome POD from a short‐term to subchronic exposure of adult rodents approximates with reasonable accuracy a concurrent and/or chronic exposure apical endpoint POD (Bianchi et al, 2021; Gwinn et al, 2020; Jackson et al, 2014; Johnson et al, 2020; LaRocca, Costa, Sriram, Hannas, & Johnson, 2020; Moffat et al, 2015; Thomas et al, 2011; Thomas et al, 2013). To our knowledge, comparison of a maternal transcriptome POD to an embryofetal apical POD within a developmental toxicity study design and derivation of a POD based upon changes in miRNA have not been published.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field of genetic toxicology is shifting toward more quantitative analyses of genetic toxicology data for potency assessments (94)(95)(96)(97). Previous work has shown that transcriptional PODs are well-aligned with apical PODs (98)(99)(100)(101). Moreover, Bemis et al (102) demonstrated the correlation between in vitro and in vivo BMDs for flow cytometric micronucleus data and suggested that the clastogenic potential of a chemical can be calculated from animal studies or cell-based models of chromosome damage.…”
Section: Discussionmentioning
confidence: 99%